Study of Bio Film Formation by Sphingomonas Paucimobilis Isolates and In-vitro Inhibition of Bio Film by Iraqi Probiotics - Shahrazad Najem Abdu-Allah (Journal of Global Pharma Technology, 2018)
Five clinical and environmental Sphingomonas paucimobilis isolates were isolated from two hospitals in Baghdad through a period extended for nine months and the identification of isolates to species level was done by Vitek-2 system. Out of 5 isolates, 2 (40%) were isolates from blood, one (20%) isolate from ear swab and 2(40%) isolates from hospital environment. The isolates showed high resistant rates 5(100%) to Ampicillin followed by Cefazolin 4(80%), while the highest sensitivity rate was 5 (100%) to Trimethoprim/Sulfamethoxazole followed by 4(80%) to Ceftazidime, Cefepime, Imipenem, Ertapenem, Ceftriaxone and Levofloxacin. Four (80%) isolates out of 5 Sphingomonas paucimobilis, were positive (+) for slime layer production while only 1(20%) isolates was negative (-) for slime layer production. Our results showed that 3(60%) Sphingomonas paucimobilis isolates (Sph2, Sph3 and Sph4) were achieved the highest thickness of biofilm forming, while 2(40%) isolates (Sph1 and Sph5) were non biofilm forming when compared with the optical density (OD) of the control by polystyrene microtitre plate method. The in vitro inhibitory effect of Iraqi probiotics (Bacillus subtilis, Lactobacillus acidophilus, Lactobacillus spp. and Saccharomyces cerevisiae) was investigated against the three highest thickness biofilm forming Sphingomonas paucimobilis isolates (Sph2, Sph3 and Sph4) and the results revealed that the absorbance (OD) of the Sphingomonas paucimobilis biofilm was declined in comparison with the data of the biofilm before the treatment with Iraqi probiotics. From the results we noticed that Iraqi probiotics were effective against the biofilm formation in all the concentrations under study and the first two concentrations (10-2 and 10-3) were the most effective. Keywords: Sphingomonas paucimobilis, Bio film formation, Bio film inhibition and Iraqi probiotics.